Wine-processed radix scutellariae alleviates ARDS by regulating tryptophan metabolism through gut microbiota - Hu, Tingting; Zhu, Ying; Zhu, Jing; Yang, Ming; Wang, Yaqi; Zheng, Qin (Frontiers in Pharmacology, 2023)
Acute respiratory distress syndrome (ARDS) is an acute and diffuse pulmonary inflammation, characterized by severe hypoxic respiratory failure caused by inflammatory tissue damage, which is a common cause of respiratory failure. Currently, there is no treatment available that can prevent or reverse the devastating effects caused by these conditions. The purpose of this study was to determine the effects of WRS on gut microbiota and the potential effect of gut microbiota on the treatment of lung disease by using a staphylococcal enterotoxin B (SEB)-induced ARDS model. The results showed that WRS could significantly reduce the pathological damage to lung and colon tissues and improve the lung and intestinal functions of ARDS mice. WRS was able to improve the level of cytokines in serum and lung tissue. Additionally, WRS could reverse the gut microbiota dysbiosis caused by SEB in ARDS mice. WRS increases the production of short-chain fatty acids (SCFAs) in the gut. This increase in SCFAs may lead to increased migration of SCFAs to the lungs and activation of free fatty acid receptors (FFAR) three and FFAR2 in lung epithelial cells, alleviating the symptoms of ARDS. Interestingly, WRS improves the faecal metabolite profiles in SEB-induced ARDS mice via tryptophan metabolism. On the basis of the component-target-metabolism strategy, baicalin, oroxylin A-7-O-glucuronide and skullcapflavon II were identified as the potential bioactive markers in WRS for the treatment of ARDS. Our study showed that WRS could ameliorate SEB-induced ARDS by regulating the structure of gut microbiota, increasing the production of SCFAs and modifying the faecal metabolite profiles through the lung-gut axis, and providing alternative treatment strategies for lung disease.